2004
DOI: 10.1038/sj.onc.1207143
|View full text |Cite
|
Sign up to set email alerts
|

Both AML1 and EVI1 oncogenic components are required for the cooperation of AML1/MDS1/EVI1 with BCR/ABL in the induction of acute myelogenous leukemia in mice

Abstract: We have previously shown that BCR/ABL, a fusion protein generated by the t(9;22)(q34;q11) translocation found in the vast majority of chronic myelogenous leukemia (CML), cooperates with AML1/MDS1/EVI1 (AME), a fusion transcription factor generated by a t(3;21)(q26;q22) translocation identified as a secondary mutation in some cases of CML during the blast phase (CML-BC), in the rapid induction of an acute myelogenous leukemia (AML) in mice. In this study, we evaluated the leukemogenic potential of EVI1-, MDS1/E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 45 publications
2
43
0
Order By: Relevance
“…EVI1 is an oncogene that is frequently associated with acute and chronic myelogenous leukemia (43)(44)(45) and has also been Figure 6. Knockdown of DACH1 expression partially restores TGF-h signaling in A547 cells.…”
Section: Discussionmentioning
confidence: 99%
“…EVI1 is an oncogene that is frequently associated with acute and chronic myelogenous leukemia (43)(44)(45) and has also been Figure 6. Knockdown of DACH1 expression partially restores TGF-h signaling in A547 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The human AME, MDS1/EVI1, EVI1, AML1/MDS1, and AML1D genes were each cloned into a bicistronic murine stem cell virus (MSCV) vector downstream of the encephalomyocarditis virus internal ribosomal entry site (IRES) and two myc tag sequences as described previously (2,20). An enhanced green fluorescent protein (GFP) gene was cloned into the EcoRI site upstream of the IRES on the MSCV vector.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments in vitro showed that overexpression of the EVI1 protein blocks granulocytic differentiation of the myeloid precursor cell line 32Dcl3, inhibits erythropoietic responsiveness in erythroid progenitors, and up-regulates the megakaryocytic differentiation of murine embryonic stem cells (16)(17)(18). In vivo, enforced expression of EVI1 using the murine Sca-1 promoter in transgenic mice impairs normal erythropoiesis and expression of EVI1 in bone marrow cells by retroviral transduction and transplantation induces either B-lymphoid malignancy with low efficiency or severe pancytopenia resembling MDS after a long latent period (19)(20)(21). These results show that aberrant expression of the EVI1 proto-oncogene plays a critical role in the pathogenesis of hematologic malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…41 In these studies, however, a potential confounding role of the vector insertion site was not addressed. Other studies speculate on necessary cooperation partners for leukemia induction by Evi1.…”
Section: Single Hit Leukemias Are Caused By Insertional Upregulation mentioning
confidence: 99%